Relationship of Knowledge, Skills, and Cadre's Guidance with The Cadre's Activeness in Family Nutrition Support at Puskesmas Barana North Belopa in 2017 - Wahyu Hidayat; Resty Ryadinency; Jumraini Jumraini (State Islamic University of Sunan Ampel, 2019)
Posyandu cadres are community members who are willing, able and have time to organize Posyandu activities in a voluntary way. Factors associated with the liveliness of Posyandu are cadre's knowledge, skills and supervision. These factors can determine the activeness of community helath center cadres (Posyandu) to family nutrition support. This study was observational with cross-sectional design, the population in this study were all cadres in 9 units Posyandu in the work area of Puskesmas Barana North Belopa Luwu Regency. Sampling was total sampling, which were 45 respondents. Data collection used questionnaires. The data collected were then processed and analyzed using univariate and bivariate analysis chi-squre test using statistic program (SPSS) 20. The table was presented in a 2x2. An univariate analysis was to find frequency distribution, in which bivariate analysis showed a correlation between knowledge and cadre's liveliness in supporting family nutrition improvement (p = ,000). There is a relationship between skill and cadre's liveliness in family nutrition support (p =,000), there is a relationship between cadre's guidance and cadre's activeness in family nutrition support (p = ,014). There is a relationship of knowledge, skills, and cadre's guidance with the cadre's activeness in family nutrition support at Puskesmas Barana North Belopa in 2017